Succeeding a family business in a transition economy: Following business goals or do it in my own way? - Ljubotina, Predrag; Omerzel, Doris Gomezelj; Vadnjal, Jaka (Serbian Journal of Management, 2018)
Students with family business background have three options once it comes to career path decision. This makes the career choice more complex compared to a classical dilemma between seeking an employment and starting a new venture. Based on GUESSS 2013/14 survey conducted in 34 countries with 109 000 participants the influence of personal factors influencing student's career choice in transition countries and countries with developed market economy in Europe was analyzed. By drawing on theory of planned behavior, risk attitudes and family business performance the difference between the two observed groups was investigated. It was found that common denominator of almost fifty years of planned economy in transition countries does influence their career choice intentions especially in terms of personal behavior control, subjective norms and risk attitudes. Findings, based on comparative approach, suggest that environmental context is an important influencing factor which should be considered in further studies of the field.